A brief historical perspective on the advent of brain oscillations in the biological and psychological disciplines. (April 2017) - Karakaş, Sirel; Barry, Robert J.
Highlights: The paper reviews the historical evolution that led to the study of the brain (body)-mind relationship on the basis of brain oscillations. It outlines and illustrates the principles of neuro-oscillatory dynamics via selected research findings. The possibility of using the oscillatory activity as biomarkers for neuropsychiatric disorders is discussed. Contribution of the academics in psychology departments to the growing research on oscillatory activity is evaluated. Abstract: We aim to review the historical evolution that has led to the study of the brain (body)-mind relationship based on brain oscillations, to outline and illustrate the principles of neuro-oscillatory dynamics using research findings. The paper addresses the relevant developments in behavioral sciences after Wundt established the science of psychology, and developments in the neurosciences after alpha and gamma oscillations were discovered by Berger and Adrian, respectively. Basic neuroscientific studies have led to a number of principles: (1) spontaneous EEG is composed of a set of oscillatory components, (2) the brain responds with oscillatory activity, (3) poststimulus oscillatory activity is a function of prestimulus activity, (4) the brain response results from a superposition of oscillatory components, (5) there are multiplicities with regard to oscillations and functions, and (6) oscillations are spatially integrated. Findings of clinical studies suggest that oscillatory responses can serve as biomarkers for neuropsychiatric disorders. However, the field of psychology is still making limited use of neuro-oscillatory dynamics for a bio-behavioral understanding of cognitive-affective processes.